2012
DOI: 10.1002/ejsp.1888
|View full text |Cite
|
Sign up to set email alerts
|

Urban district identity as a common ingroup identity: The different role of ingroup prototypicality for minority and majority groups

Abstract: In this paper, we examined how identification with urban districts as a common ingroup identity and perceived ingroup prototypicality influence the attitudes of residents toward other ethnic groups in their neighborhood. The overall conclusion of two field studies (N = 214 and N = 98) is that for majority‐group members, there may be a positive relation between identification with an overarching identity and outgroup attitudes but only when they perceive their ingroup as low in prototypicality for the overarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
(71 reference statements)
6
29
0
Order By: Relevance
“…As expected, the pattern was reversed for the negatively valued inclusive category. Prototypicality judgments are therefore contextdependent and affected by reality constraints (e.g., Spears, Jetten, & Doosje, 2001;Ufkes et al, 2012). These results replicate, but also go beyond, previous research (Devos & Banaji, 2005;Devos, Gavin, & Quintana, 2010; as they show such constraints for prototypicality also within negative inclusive categories.…”
Section: Discussionsupporting
confidence: 83%
“…As expected, the pattern was reversed for the negatively valued inclusive category. Prototypicality judgments are therefore contextdependent and affected by reality constraints (e.g., Spears, Jetten, & Doosje, 2001;Ufkes et al, 2012). These results replicate, but also go beyond, previous research (Devos & Banaji, 2005;Devos, Gavin, & Quintana, 2010; as they show such constraints for prototypicality also within negative inclusive categories.…”
Section: Discussionsupporting
confidence: 83%
“…; Ufkes et al. ). This describes how the formation of a common identity decreases prejudices and creates positive feelings toward formerly out‐group members.…”
Section: Resultsmentioning
confidence: 97%
“…Ufkes () and Ufkes et al. () did empirical research on neighborhood identity as a common identity for inhabitants with different ethnic and cultural backgrounds. He found that people who identify more with the neighborhood had more positive ideas about people from other ethnic groups (Dukes and Musterd ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has established that identifi cation with a superordinate category only improves minority group members' out-group attitudes when they perceive their group as prototypical for the overarching group (Ufkes, Otten, Van der Zee, Giebels, & Dovidio, 2012 ). Moreover, for Serbs the common in-group may pose threats to the distinctiveness of their ethnic group.…”
Section: Discussionmentioning
confidence: 99%